Protein degradation and defense against neurodegenerative disease 2 - Goldberg, Alfred (Henry Stewart Talks, 2014)
The 26S proteasome, The 20S proteasome, Proteasome inhibitors, PS-341, Proteasome inhibitors in multiple myeloma, Structures of the archaeal PAN ATPase-20S complex and the eukaryotic 26S proteasome, Multiple ATP-dependent steps in proteasome function, The gating mechanism of the proteasome, Prions inhibit proteasome function, Binding of ubiquitin conjugates activate the 26S proteasome by stimulating 20S gate-opening and ATP hydrolysis, Ubiquitin conjugates activate their own degradation by the 26S Proteasome, The inhibitor of proteasome-associated deubiquitinating enzyme Usp14, IU1, enhances degradation of tau